2017
DOI: 10.1038/s41598-017-17729-9
|View full text |Cite
|
Sign up to set email alerts
|

The Toll–Like Receptor 2/6 Agonist, FSL–1 Lipopeptide, Therapeutically Mitigates Acute Radiation Syndrome

Abstract: Risks of radiation exposure from nuclear incidents and cancer radiotherapy are undeniable realities. These dangers urgently compel the development of agents for ameliorating radiation–induced injuries. Biologic pathways mediated by myeloid differentiation primary response gene 88 (MyD88), the common adaptor for toll–like receptor (TLR) and Interleukin–1 receptor signaling, are critical for radioprotection. Treating with agonists prior to radiation enhances survival by activating TLR signaling, whereas radiomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In addition, damage of radiation exposure from cancer radiotherapy is unavoidable ( Singh et al, 2015 ). Of note, activation of TLRs can also contribute to hematopoietic replenishment as its up-regulation of growth factor G-CSF, alleviating the intrinsic repair to radiant injuries ( Singh et al, 2012 ; Kurkjian et al, 2017 ).…”
Section: Tlrs and Immune Systemmentioning
confidence: 99%
“…In addition, damage of radiation exposure from cancer radiotherapy is unavoidable ( Singh et al, 2015 ). Of note, activation of TLRs can also contribute to hematopoietic replenishment as its up-regulation of growth factor G-CSF, alleviating the intrinsic repair to radiant injuries ( Singh et al, 2012 ; Kurkjian et al, 2017 ).…”
Section: Tlrs and Immune Systemmentioning
confidence: 99%
“…Kurkjian et al reported that the synthetic TLR2/6 agonist, fibroblast-stimulating lipopeptide (FSL-1), prolonged survival in male and female mice after 24 h of radiation 64 . FSL-1 has been shown to not only promote hematopoiesis in bone marrow, spleen, and periphery but also to increase systemic levels of hematopoiesis-stimulating factors 65 .…”
Section: Combined Application Of Tlrs With Other Cancer Treatmentsmentioning
confidence: 99%
“…PSK has significantly inhibited the breast cancer growth via stimulation of CD8 T cells and natural killer (NK) cells. Other TLR2 agonists or their modified forms, lipopeptides also have been reported to be useful for the cancer treatment, which further suggests the potential of TLR2 agonist as effective enhancers for cancer immunotherapies . However, the current known TLR2 agonists, lipopeptides or their derivatives, are having limitations because of the difficulties in synthesis, susceptibility to hydrolysis, as well as in eliciting inflammatory cytokine storm.…”
mentioning
confidence: 99%